Conceptual design of low-boom low-drag supersonic transports - Sun, Yicheng; Smith, Howard; Chen, Haixin (American Institute of Aeronautics and Astronautics (AIAA), 2020)
This paper introduces a supersonic aircraft design model developed in a multidisciplinary design analysis and optimization (MDAO) environment. Low- to medium- fidelity methods are applied to the conceptual design model. A family of different classes supersonic aircraft are designed with similar general layout, including a single seat supersonic demonstrator, a 10-passenger supersonic business jet and a 50-seat supersonic airliner. These concepts prove the feasibility of low-boom low-drag supersonic transport designs in a multidisciplinary perspective. There are some challenges to balance the volume with packaging and control requirements. The low-boom design for configuration with nacelles are also very challenging.